Muscle damage, metabolism, and oxidative stress in mdx mice: Impact of aerobic running. Issue 1 (14th June 2016) - Schill, Kevin E.; Altenberger, Alex. R.; Lowe, Jeovanna; Periasamy, Muthu; Villamena, Frederick A.; Rafael‐Fortney, JIll A.; Devor, Steven T.
ABSTRACT: Introduction: We tested how a treadmill exercise program influences oxygen consumption, oxidative stress, and exercise capacity in the mdx mouse, a model of Duchenne muscular dystrophy. Methods: At age 4 weeks mdx mice were subjected to 4 weeks of twice‐weekly treadmill exercise. Sedentary mdx and wild‐type mice served as controls. Oxygen consumption, time to exhaustion, oxidative stress, and myofiber damage were assessed. Results: At age 4 weeks, there was a significant difference in exercise capacity between mdx and wild‐type mice. After exercise, mdx mice had lower basal oxygen consumption and exercise capacity, but similar maximal oxygen consumption. Skeletal muscle from these mice displayed increased oxidative stress. Collagen deposition was higher in exercised versus sedentary mice. Conclusions: Exercised mdx mice exhibit increased oxidative stress, as well as deficits in exercise capacity, baseline oxygen consumption, and increased myofiber fibrosis. Muscle Nerve 54 : 110–117, 2016